MENEMUKAN KESEJAHTERAAN PSIKOLOGIS DIBALIK PROFESI DOSEN : PSYCHOLOGICAL CONTRACT SEBAGAI SALAH SATU PREDIKTOR TERCAPAINYA PSYCHOLOGICAL WELL BEING PADA DOSEN - Sulistiobudi, Rezki Ashriyana; Kadiyono, Anissa Lestari; Batubara, Megawati (Universitas Ahmad Dahlan, 2017)
Profession as lecturer has the specific characteristic and responsibilities in running Tridharma Perguruan Tinggi, which is to conduct education, research, and community service. Role as a lecturer is very important in promoting next generation to better future. This study aims to determine how the influence of the psychological contract on the psychological well-being of lecturers in educational institutions. The psychological contract is formed on the belief that the organization's employees will appreciate the contribution and to meet expectations. This belief will create positive work experiences and form a psychological sense of security. The realization of the psychological contract can bring balance and harmony at employees in the work, optimizing organizational productivity, building a good relationship between the employee and the organization, and minimize conflict and social inequality in organization. This condition is identical to the psychological well-being. The results showed that there is a low gap on transactional contract and relational contract. It can be said that perceived fulfillment is not optimal in a few aspects. On the dimension of psychological wellbeing, lecturers perceive that personal growth and personal life that provide the greatest contribution. The result of the influence of the psychological contract and psychological wellbeing show that there is significant influence, which means that the lower the gap fulfillment of obligations by the institution will have an impact on increasing positive feelings of the individual. This will lead to the attainment of the psychological well-being of lecturers. AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana pengaruh kontrak psikologis terhadap kesejahteraan psikologis pada tenaga pendidik di institusi pendidikan. Hubungan timbal balik atau kontrak psikologis terbentuk dari keyakinan karyawan bahwa organisasi akan menghargai kontribusi dan memenuhi harapannya. Keyakinan ini akan menciptakan pengalaman kerja yang positif dan membentuk rasa aman secara psikologis. Terwujudnya kontrak psikologis dapat memunculkan keseimbangan, keselarasan, keserasian, kelancaran karyawan dalam bekerja, kemajuan organisasi, hubungan yang baik antara karyawan dan organisasi, serta meminimalisir munculnya konflik dan kesenjangan sosial. Kondisi ini identik dengan kesejahteraan psikologis. Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara psychological contract dan psychological well being. Rendahnya gap antara kebutuhan dan pemenuhan baik pada transactional dan relational contract bermakna rendahnya psychological contract breach yang dirasakan oleh dosen. Semakin rendah tingkat pengingkaran yang dirasakan maka akan semakin tinggi tingkat psychological well being mereka. Hal ini akan berdampak pada peningkatan perasaan yang lebih positif. Dosen merasa bahwa faktor personal growth dan personal life lah yang memberikan kontribusi terbesar terhadap kesejahteraan psikologis mereka.